Real time 3D echocardiography for evaluation of systolic dyssynchrony index in patients with dilated cardiomyopathy and acute myocardial infarction - Khetan, Divij (International Journal of Research in Medical Sciences, 2018)
Background: In recent years, real time 3D echocardiography (RT3DE), a novel and non-invasive method has catched the eyes of various cardiologists for evaluating ventricular dyssynchrony. The main aim of the present study was to establish applicability of RT3DE for the assessment of ventricular dyssynchrony in patients with dilated cardiomyopathy (DCMP) and acute myocardial infarction (AMI). Methods: It was a hospital based observational and comparative study which included total 105 patients. Among all the patients, 35 with DCMP, 35 with AMI and 35 healthy patients were included. Various electrocardiographic, 2D and 3D echocardiography parameters were evaluated. Percentage ventricular systolic dyssynchrony index (SDI) was estimated using RT3DE to define ventricular dyssynchrony. The correlation of SDI with left ventricular ejection fraction (LVEF) and QRS duration of all patients was calculated using Pearson correlation co-efficient and regression equation. Results: Age distribution among all three groups was non-significant with mean age 53.56±12.11 years. The RT3DE displayed significantly higher SDI (p=0.001) in DCMP group (16.67±5.81 %) followed by AMI group (8.6±2.2%) and control group (3.14±1.0%). The value of QRS duration was also higher (>140ms) in DCMP patients (142.40±34.71ms) and lower (>120ms) in AMI (108.85±20.67ms) and healthy patients (91.08±8.88ms). No significant correlation of SDI with LVEF among all three groups was observed. Conclusions: The results added more practicality of RT3DE for estimation of ventricular dyssynchrony in patients with varied cardiac conditions and also displayed its utility as an appropriate guide for cardiac resynchronization therapy.